2018
DOI: 10.4149/neo_2018_171028n691
|View full text |Cite
|
Sign up to set email alerts
|

Expression of autophagy genes in acute myeloid leukemia: associations with clinical characteristics and prognosis

Abstract: The relationships between autophagy-associated gene expression and clinical characteristics and prognosis in acute myeloid leukemia (AML) have not been well revealed. We examined mRNA expression of Bcl-2, p62, Beclin 1, VPS34, Rubicon, ALFY, UVRAG, ULK1, LC3 and NBR1 in 20 AML cases and 10 benign hematological cases by real-time PCR. Clinical information, treatment responses and outcomes of the AML patients were collected. Beclin 1, LC3, UVRAG, Rubicon and NBR1 were downregulated in AML patients compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…RUBICON expression is significantly decreased in AML cases compared with control group 33 . Accordingly, an involvement of autophagy pathway in the outcome of AML leukemia has been suggested.…”
Section: Discussionmentioning
confidence: 81%
“…RUBICON expression is significantly decreased in AML cases compared with control group 33 . Accordingly, an involvement of autophagy pathway in the outcome of AML leukemia has been suggested.…”
Section: Discussionmentioning
confidence: 81%
“…In neoplastic cells however, autophagy sustains survival and proliferation upon exposure to intracellular and environmental stress, hence supporting tumor growth, invasion, and metastatic dissemination 6 . The deregulation of autophagy has been reported in AML [7][8][9][10] . Historical and new treatments have been shown to induce autophagy, which may be protective or participate in cell death depending on the compound [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 97%
“…Unfortunately, this would result in only a few patients being enrolled in our study, and the statistical power could, therefore, be significantly reduced. Of note, Liang et al 43 also observed a trend toward higher ULK1 mRNA levels in the AML patients compared with the patients with benign hematological diseases. Subsequently, we centered on the molecular mechanism underlying ULK1 high expression in NPM1-mutated AML.…”
Section: Discussionmentioning
confidence: 89%